IDDF2019-ABS-0168 Bone and renal safety are improved in chronic hbv patients 1 year after switching to tenofovir alafenamide (TAF) from tenofovir disoproxil fumarate (TDF). (June 2019) - Lik Yuen Chan, Henry; Seto, Wai Kay; Buti, Maria; Izumi, Namiki; Lim, Young-Suk; Kao, Jia-Horng; Streinu-Cercel, Adrian; Nurmukhametova, Elena; Ma, Xiaoli; Tabak, Fehmi; Jablkowski, Maciej; Suri, Vithika; et al.
Abstract : Background: TAF has shown efficacy non-inferior to that of TDF at Week 96 with less bone and renal effects. Following implementation of a protocol amendment to extend double-blind (DB) treatment for an additional year, 50% of patients were able to continue on DB treatment while the remainder had already rolled-over to open-label (OL) TAF at Week 96. Here we compared the efficacy and safety from Week 96 to 144 in patients randomized to TDF in whom treatment was either continued or switched to TAF at Week 96. Methods: In 2 identically-designed studies, 1298 HBeAg-negative and HBeAg-positive CHB patients (873 TAF, 425 TDF) were randomized and treated. In the TDF group, 211 remained on TDF (DB TDF) while 180 patients were switched to OL TAF (TDF→TAF) at Week 96. Safety assessments including changes in bone (hip and spine BMD) and renal (CrCl by Cockcroft-Gault [eGFRCG ], serum creatinine) parameters, viral suppression, and biochemical responses were assessed in all patients from Week 96 to Week 144. Results: Patient characteristics were similar for those who continued TDF and those switched to TAF. In the TDF→TAF group, improvements in eGFRCG were observed, while those remaining on DB TDF showed a continued decrease in eGFRCG at Week 144 (table 1 ). Similarly, significant improvements in hip and spine BMD were seen over 1 year in TDF→TAF patients while those remaining on TDF either had continued BMD declines or smaller increases (figure 1 ). High rates of virologic suppression (HBV DNA <29 IU/mL) were maintained in both groups (TDF→TAF 84% and DB TDF 88%; M=F), while a greater rate of ALT normalization (by 2018 AASLD criteria) was seen in TDF→TAF patients at 1 year following switch (45% vs 29%; M=F). Conclusions: Virologic control was maintained and ALT normalization was increased following switch from TDF to TAF. However, compared to those remaining on TDF for an additional year, patients switched to TAF had improved bone and renal safety.